Ceramika grafitowa z Ostrowa Tumskiego w Poznaniu - Ruminiecka, Julia; Sikorski, Andrzej; Wenzel, Julia (Folia Praehistorica Posnaniensia, 2018)
The article’s objective is to present the first graphite goods found at the princely part of the Poznań stronghold. Pottery fragments, a disc with a hole made of graphite sherd, and spindle whorl have been discovered at the foundations of the Mieszko I palatium, next to the remains of a goldsmith’s workshop. Relatively straightforward stratigraphy, despite later destruction caused by numerous construction phases of the Sacred Mary Church, along with accompanied artifacts from the layers, make possible to date these finds to the period stretching from the 10 -1 1th to the 12th 13th centuries and regard them as ‘imports’ from the south. Besides the 12th century settlement at Szeląg, this is the second site in Poznań where this characteristic type of pottery has been found.